2015
DOI: 10.1111/modl.12213
|View full text |Cite
|
Sign up to set email alerts
|

Leveling L2 Texts Through Readability: Combining Multilevel Linguistic Features with the CEFR

Abstract: Selecting appropriate texts for L2 (second/foreign language) learners is an important approach to enhancing motivation and, by extension, learning. There is currently no tool for classifying foreign language texts according to a language proficiency framework, which makes it difficult for students and educators to determine the precise difficulty/complexity levels of an unclassified text. Taking the Chinese language as an example, this study aimed to create a readability assessment system, called the Chinese R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 59 publications
(70 reference statements)
0
25
0
1
Order By: Relevance
“…Sung et al. () had five experienced teachers classify 1,578 texts sampled from representative textbooks into six levels in the Common European Framework of Reference for Languages (CEFR) in terms of text complexity; they then analyzed the texts using 30 linguistic features representative of lexical, syntactic, semantic, and cohesion dimensions with a support vector machine model to determine how well they could predict the CEFR levels of the texts. Their results showed that all individual features had significant predictive power; that the best accuracy was achieved by a model with 25 of the 30 features; and that, strikingly, three lexical complexity features alone were able to achieve an accuracy of 65%.…”
Section: Text Adaptation and Benchmarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Sung et al. () had five experienced teachers classify 1,578 texts sampled from representative textbooks into six levels in the Common European Framework of Reference for Languages (CEFR) in terms of text complexity; they then analyzed the texts using 30 linguistic features representative of lexical, syntactic, semantic, and cohesion dimensions with a support vector machine model to determine how well they could predict the CEFR levels of the texts. Their results showed that all individual features had significant predictive power; that the best accuracy was achieved by a model with 25 of the 30 features; and that, strikingly, three lexical complexity features alone were able to achieve an accuracy of 65%.…”
Section: Text Adaptation and Benchmarksmentioning
confidence: 99%
“…Vajjala and Meurers (2012) evaluated the effectiveness of 19 lexical features, 25 syntactic complexity measures, and 2 traditional text readability measures for predicting the grade level of reading texts, and reported an accuracy of 86.7%, 75.3%, and 38.8%, respectively, for each of the three types, and an overall accuracy of 93.3% with all features combined. Sung et al (2015) had five experienced teachers classify 1,578 texts sampled from representative textbooks into six levels in the Common European Framework of Reference for Languages (CEFR) in terms of text complexity; they then analyzed the texts using 30 linguistic features representative of lexical, syntactic, semantic, and cohesion dimensions with a support vector machine model to determine how well they could predict the CEFR levels of the texts. Their results showed that all individual features had significant predictive power; that the best accuracy was achieved by a model with 25 of the 30 features; and that, strikingly, three lexical complexity features alone were able to achieve an accuracy of 65%.…”
Section: Text Adaptation and Benchmarksmentioning
confidence: 99%
“…The annotations and benchmark ranges incorporated in the online text adaptation tool are easily manageable by teachers but reflect limited dimensions of the text complexity construct (Crossley et al., ; Sung et al., ). Additional types of annotations and benchmark ranges can be explored in the future; for example, for syntactic complexity (Lu, ).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…A critical consideration in this process that directly bears upon learners’ literacy development is to ensure the linguistic complexity of the reading texts is suitable for their expected proficiency levels (Crossley, Allen, & McNamara, ; Hiebert & Mesmer, ). Matching texts to particular proficiency levels is challenging even for experienced teachers (Sung, Lin, Dyson, Chang, & Chen, ). With the advent of corpus techniques, numerous data‐driven indices are now available for characterizing text complexity (Crossley, Greenfield, & McNamara, ; Graesser, McNamara, & Kulikowich, ; Lu, ).…”
mentioning
confidence: 99%
“…Most of corpus linguistics research has concentrated on analyzing lexical and syntactical features in written texts in order to understand the complexity of edited texts (Sung, Lin, Dyson, Chang, & Chen, 2015), characteristics of language use in specific domains (Biber et al, 2004), or quality of learner texts in terms of lexical diversity, sophistication, and accuracy, or syntactical complexity, range and accuracy. Correspondingly, these features have attracted the most effort in the machine analysis of linguistic features.…”
Section: Future Directionsmentioning
confidence: 99%